2016
DOI: 10.3892/mmr.2016.5289
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide exhibits cardioprotective effects by decreasing endoplasmic reticulum stress in a diabetic cardiomyopathy rat model

Abstract: Abstract. Endoplasmic reticulum (ER) stress is critical in the occurrence and development of diabetic cardiomyopathy (DC). Hydrogen sulfide (H 2 S) has been found to be the third gaseous signaling molecule with anti-ER stress effects. Previous studies have shown that H 2 S acts as a potent inhibitor of fibrosis in the heart of diabetic rats. This study aimed to demonstrate whether H 2 S exhibits protective effects on the myocardium of streptozotocin (STZ)-induced diabetic rats by suppressing ER stress. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…In a previous study, H 2 S was shown to decrease oxidative stress, protect against mitochondrial injury, activate autophagy, promote the clearance of ubiquitin aggregates, suppress endoplasmic reticulum stress, and ultimately facilitate cardioprotection in DCM. These changes involve multiple signaling pathways, and accordingly, H 2 S has been shown to activate the AMPK/rapamycin (mTOR) signaling pathway (F. Yang et al, 2017), increase Keap1 expression by suppressing its ubiquitylation (Wu et al, 2017), reduce the expression of glucose-regulated protein (Grp78), C/EBP-homologous protein (CHOP), and caspase-12 (F. Li et al, 2016), and inhibit the TLR4/NF-κB pathway and the F I G U R E 5 H 2 S treatment increases the levels of Akt and FoxO1 phosphorylation and inhibits FoxO1 nuclear translocation in H9C2 cells with Akt inhibitor pretreatment. H9C2 cells were pretreated with the Akt inhibitor MK-2206 2HCl (2.5 μM) for 1 hr, treated with GYY4137 (100 μM) for 30 min, and then exposed to HG for an additional 36 hr.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, H 2 S was shown to decrease oxidative stress, protect against mitochondrial injury, activate autophagy, promote the clearance of ubiquitin aggregates, suppress endoplasmic reticulum stress, and ultimately facilitate cardioprotection in DCM. These changes involve multiple signaling pathways, and accordingly, H 2 S has been shown to activate the AMPK/rapamycin (mTOR) signaling pathway (F. Yang et al, 2017), increase Keap1 expression by suppressing its ubiquitylation (Wu et al, 2017), reduce the expression of glucose-regulated protein (Grp78), C/EBP-homologous protein (CHOP), and caspase-12 (F. Li et al, 2016), and inhibit the TLR4/NF-κB pathway and the F I G U R E 5 H 2 S treatment increases the levels of Akt and FoxO1 phosphorylation and inhibits FoxO1 nuclear translocation in H9C2 cells with Akt inhibitor pretreatment. H9C2 cells were pretreated with the Akt inhibitor MK-2206 2HCl (2.5 μM) for 1 hr, treated with GYY4137 (100 μM) for 30 min, and then exposed to HG for an additional 36 hr.…”
Section: Discussionmentioning
confidence: 99%
“…The irreversible and progressive pulmonary fibrosis leading to respiratory function failure is still the main cause of PQ‐induced death (Dinis‐Oliveira et al, ). Recently, increasing evidence indicates that plasma H 2 S is low level in several animal models of fibrotic diseases and a supplement of exogenous H 2 S is able to ameliorate fibrosis in the kidney (Han et al, ; L. Li et al, ; Li, Li, Zeng, Liu, & Yang, ), heart (Li et al, ; Liang et al, ; Liu et al, ), liver (Mani, Cao, Wu, & Wang, ), peritoneum (Lu et al, ), skin and lung (Fang et al, ; Wang et al, ). As a significant process towards fibrogenesis, EMT characterizes the morphological changes associated with the downregulation of epithelial cell markers, such as E‐cadherin, and upregulation of mesenchymal markers, such as vimentin (Cannito et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…ER-stress is one of the underlying mechanisms of cardiac dysfunction including diabeticcardiomyopathy (27)(28)(29). Studies suggest that there is relationship between S(E)R function and cytosolic Zn 2+ level in diabetic rat cardiomyocytes (29; 30).…”
Section: +mentioning
confidence: 99%